Essence limit citizens' constitutional rights during operational search activities - Назаров, Віктор Володимирович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
In work probed essence of limitation of constitutional rights for citizens in operatively-search activity, character of plenary powers of organs which carry out operatively-search activity, suggestions are borne in relationto perfection of current legislation in relation to limitation of constitutional rights for citizens during conducting operatively-search measures.